Análisis de los parámetros para la extracción del polen de las flores masculinas, en el cultivo de palma aceitera (Elaeis guineensis; Jacq) - Pacheco Ulloa, Marcos Agustín (2022)
This document deals with the parameters of pollen extraction in the cultivation of oil palm (Elaeis guineensis Jacq). It is necessary to highlight that the conclusions determined that the oil palm produces male and female flowers in different inflorescences and separately on the same plant, in such a way that it is necessary to transfer the pollen from one flower to another. Therefore, pollinating agents are needed to ensure good fruit set; The date palm can be pollinated naturally by the wind, bees and other insects, but this type of pollination does not guarantee high yields, so an artificial technique is necessary for its commercial production, because with this technique the increase in bunch weight can represent an average of 25 % and the operation is very profitable; Pollination is of great importance for the yield of this crop, since when it is deficient, poor bunch formation, abortions and rotting, loss in average biomass, low production and low oil extraction can occur and the most common method to extract the oil palm pollen is: Extraction of male inflorescences (the inflorescences are placed on top of wire mesh trays or shelves with a container below to catch the dried pollen that falls from the flowers, this method being the most common) and the mechanical extractor of pollen (the automation of this machine can vary, but it is usually made up of a rotating barrel into which the mature inflorescences are introduced and an agitator to filter the pollen from other materials).